Pétain-Laval : the conspiracy - Cecil, Robert (London : Constable and Co., 1942)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Laval, Pierre; Pétain, Philippe; Wereldoorlog 2; collaboratie; Frankrijk